Arabic Language Acquisition as a Foreign Language for Non-Native Speaker Students in PBA UIN Maulana Malik Ibrahim Malang - Editia, Qushayyi Akbar; Nabilah, Yulyana Dewi; Hafidz, Abdurrahman (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
Language acquisition is an important aspect in understanding humans learn and communicate. Arabic language acquisition as a second language is the process of learning and using Arabic by individuals who are not native Arabic speakers, but choose to learn and master an additional or second language. The purpose of this study is to determine the acquisition of Arabic as a foreign language for non-native speaker students at PBA UIN Maulana Malik Ibrahim Malang as well as the supporting factors in the process of language acquisition. This research uses a descriptive qualitative approach. Data were obtained by interview and observation techniques from primary data sources. The informants of this study were taken from four non-native speaker students of PBA UIN Malang. The results of this study indicate that there are two language acquisition carried out by students, namely; 1) Utilisation of technology and 2) Interaction with peers. The things that support the process of foreign language acquisition are; 1) campus policy, 2) learning environment. As for the inhibiting factors in the process of foreign language acquired in the scope of non-native students of PBA UIN maulana malik Ibrahim malang, namely; 1) lack of socialisation of the curriculum, 2) Low language skills.